Characteristics and Dosimetric Properties of Tissue-Equivalent Thermoluminescent Glass Detector Based on Al-Li-Zn, Borate Oxide Dope Dy3+ - Efenji, Godwin Irinam; Bin Mustapha, Iskandar Shahrim; Yusof, Nur Nabihah; Anthony, Rabba James; Kamgba, Ferdinand Ayim; P. O., Ushie; Hussein Khazaalah, Thair; Jamil , Munirah; Izwan, Muhammad Fadhirul; Aliyu, Umar Sa’ad; Ezra, Nabasu Seth; Oke, Aduragbemi Olaoluwa; Salah Naeem , Hayder; Muhammad , Alhassan; Idriss , Ali S. A. (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Functionality and dosimetric properties of a tissue-equivalent thermoluminescent glass detector doped with Dy3+. This work investigated an Aluminium-Lithium-Zinc borate oxide matrix using the melting-quench method. X-ray diffraction confirms the glass sample is amorphous. Dysprosium ions doping raises the glass’s tissue equivalent effective atomic number (Zeff.), improving its ability to absorb radiation and its sensitivity, with reproducibility almost at the tolerable limit. The glass detector also reduces the fading rate and signal loss over time. The minimum detectable dose values were 53.04 mGy and 45.1 mGy for the un-doped and 1.5 mol Dy3+ doped Al-Li-Zn borate glasses, respectively. A bright peak was seen in photoluminescence spectra at 348 nm (yellow), 529 nm (green), and 625 nm (orange hue). These correspond to the Dy3+ transitions at 4H15/2 → 6P7/2, 4F9/2 → 6H15/2, 4F9/2 → 6H15/2, and 4F9/2 → 6H13/2 , respectively. There was a noticeable drop in Tg from 257°C in the undoped sample to 101°C in the doped sample, Tm from 862°C to 815°C, and Tc from 756°C to 444°C in the doped sample. These results may indicate a lower temperature at which the material transitions from a solid to a liquid state and a lower crystallisation threshold. The frequency component and energy of activation of the 1.5 mol Dy3+ doped Aluminium-Lithium-Zinc borate are 2.1×10 27 s-1 and 1.03 eV, respectively. The 1.5 Dy3+ doped Aluminium-Lithium-Zinc borate glasses exhibit promising dosimetric properties of the tissue-equivalent thermoluminescent glass detector, indicating its potential for accurate and consistent radiation dosimetry in various applications.